2005
DOI: 10.1021/ja042172s
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle Formed by Amphiphilc Cucurbit[6]uril:  Versatile, Noncovalent Modification of the Vesicle Surface, and Multivalent Binding of Sugar-Decorated Vesicles to Lectin

Abstract: We report a novel vesicle formed by an amphiphilic CB[6] derivative, the surface of which can be easily modified via host-guest interactions by taking advantage of molecular cavities, readily accessible at the vesicle surface, and their strong affinity toward polyamines. Amphiphilic CB[6] derivative 1 synthesized by reaction between (allyloxy)12CB[6] and 2-[2-(2-methoxyethoxy)ethoxy]ethanethiol affords a vesicle that has been characterized by TEM, light scattering, and fluorescent dye entrapment experiments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(101 citation statements)
references
References 25 publications
1
97
0
3
Order By: Relevance
“…The TLC analysis showed three well separated spots with a ratio of 3(s1):1(s2):1(s3), which corresponded to the normal cucurbit [5,6,7]urils (Q [5], Q [6], Q [7], Figure 1). The typical guest probe tests showed that the substituted s3 cucurbit[n]uril(s) were not SQ [7], but rather SQ [6], because no included 1-adamantaneamine (ad) resonance signals were observed in the 1 H-NMR spectrum of the s3-ad system [23], while the 1 H-NMR spectra exhibited two sets of signals for the bound (indicated by wedges) and unbound protons of the HCl salt of 2,2'-bispyridine (bpy·1HCl) which suggested that the s3 was definitely SQ [6]s [24].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The TLC analysis showed three well separated spots with a ratio of 3(s1):1(s2):1(s3), which corresponded to the normal cucurbit [5,6,7]urils (Q [5], Q [6], Q [7], Figure 1). The typical guest probe tests showed that the substituted s3 cucurbit[n]uril(s) were not SQ [7], but rather SQ [6], because no included 1-adamantaneamine (ad) resonance signals were observed in the 1 H-NMR spectrum of the s3-ad system [23], while the 1 H-NMR spectra exhibited two sets of signals for the bound (indicated by wedges) and unbound protons of the HCl salt of 2,2'-bispyridine (bpy·1HCl) which suggested that the s3 was definitely SQ [6]s [24].…”
Section: Resultsmentioning
confidence: 99%
“…The chemistry of cucurbit[n]uril (Q[n]s) has expanded dramatically with the discovery of cucurbituril(Q [6]) and its homologues (Q [5], Q [7], Q [8], and Q [10]) [1][2][3]. Recently, the direct functionalization of CB[n] [4][5][6] and introduction of building blocks for the preparation of Q[n] derivatives [7][8][9] and analogues [10][11] providing CB[n]s with solubility in both organic and aqueous solution has further expanded the range of the research and applications, which have been summarized in related reviews [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations